Mental visualization and its Relationship to Skills of Passing and Scoring From a Jump in Basketball for Female Students - Ibrahim Bahram Khurshid Muhammad Ali (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
The research aimed to identify level of mental imagery among second-year female students at faculty of Physical Education and Sports Sciences, University of Kirkuk, and to determine accuracy of their basketball passing and jump scoring skills. It also sought to identify correlation between mental imagery and these basket ball passing and scoring skills among research sample. The researcher used a descriptive approach with correlational analysis, as it was suitable for nature of research. The research population was selected purposively from second-year female students at faculty of Physical Education and Sports Sciences, University of Kirkuk, during 2024-2025 academic year, divided into one section, totaling (60) students. The research sample was randomly selected from (26) students, resulting in a final sample size of (26) students, representing (43.33%) of original population. The results showed a statistically significant positive correlation between level of mental imagery and accuracy of students' performance in basketball passing and jump scoring skills. Mental imagery contributes to improving students' ability to execute these skills accurately. The highest, indicating effectiveness of this strategy in developing skill performance, it is recommended to incorporate regular mental visualization sessions into basketball training programs with aim of enhancing skill performance, especially in skills of handling and jump scoring , and to organize specialized training workshops for coaches to teach mental visualization strategies and how to apply them effectively with players, and to urge students to practice mental visualization daily before or after training, with a focus on accurately imagining movements and skills.